Analysis of Poverty Reduction in East Barito Regency (Universitas Negeri Semarang, 2022)
Poverty is a problem that exists in all parts of the world and has a negative impact on economic growth. With several factors of poverty that have the potential to have an influence; in the form of economic growth, population, unemployment, as well as the human development index how much influence it has on poverty in East Barito Regency. Therefore we analyze what factors influence poverty reduction. Based on data from BPS East Barito Regency for 2011-2021, using the OLS analysis tool, eviews 12. The results of this study show that economic growth has a positive effect on poverty, which means that economic growth is uneven and concentrated in certain sectors. Unemployment and the human development index in East Barito have a negative effect on poverty, this shows that there is a lack of financial, educational and health resources to improve people's welfare. Compared to the total population which has no effect on poverty in East Barito district, the cause of the reduction in poverty in East Barito is not solely due to population, but to an increase in the availability of quality economic resources for the community.